(untitled) (The Journal of Plant Protection Sciences, 2021)
Okra (Abelmoschus esculentus) is one of the insect pests, one mite and four natural enemies most important vegetables grown in subtropical in Mizoram. Among them, the Mylabris part of India. It is grown in India over an area of pustulata and Dysdercus cingulatus were found 3.25 lakh ha with annual production of 33.8 lakh as major pest. The incidence of Mylabris tones. In Mizoram, it is cultivated over 2749 ha pustulata and Dysdercus cingulatus were with annual production of 11270.9 MT during noticed during reproductive stage and attained 2008-2009. Okra is subjected to attack of as the peak level of infestation on first week of July many as twenty insect and non-insect pests in the and first week of August. The second most country, which accounts for 8 to 76 percent loss important and dominant insect pest was in yield (3). An attempt was made to study the Nodostoma sp. and was also categorized as pest complex and their succession in okra under major insect pests of okra and it was noticed subtropical climatic conditions of Mizoram.